2011
DOI: 10.1074/jbc.m111.275495
|View full text |Cite
|
Sign up to set email alerts
|

miR-200a Regulates Nrf2 Activation by Targeting Keap1 mRNA in Breast Cancer Cells

Abstract: NF-E2-related factor 2 (Nrf2) is an important transcription factor that activates the expression of cellular detoxifying enzymes. Nrf2 expression is largely regulated through the association of Nrf2 with Kelch-like ECH-associated protein 1 (Keap1), which results in cytoplasmic Nrf2 degradation. Conversely, little is known concerning the regulation of Keap1 expression. Until now, a regulatory role for microRNAs (miRs) in controlling Keap1 gene expression had not been characterized. By using miR array-based scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(192 citation statements)
references
References 50 publications
9
182
1
Order By: Relevance
“…The latter might play a critical role in maintaining Nrf2 pathway activation for an extended period of time, which is beneficial for tissue repair since It is well established that Keap1 regulates the Nrf2 signaling pathway, but the regulation of Keap1 itself is less well documented. Recent studies showed that Keap1 is subjected to posttranscription regulation: its mRNA level was affected by microRNA 200a through its 3= untranslated region (32,33). Another study reported that Keap1 overexpression in HepG2 cells inhibits Nrf2 activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…The latter might play a critical role in maintaining Nrf2 pathway activation for an extended period of time, which is beneficial for tissue repair since It is well established that Keap1 regulates the Nrf2 signaling pathway, but the regulation of Keap1 itself is less well documented. Recent studies showed that Keap1 is subjected to posttranscription regulation: its mRNA level was affected by microRNA 200a through its 3= untranslated region (32,33). Another study reported that Keap1 overexpression in HepG2 cells inhibits Nrf2 activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…BCRP/ABCG2, another important efflux transporter in ADME and MDR, is also regulated by a number of miRNAs via direct or indirect mechanisms ( Table 2). The MDR of S1 colon carcinoma cell line is Zhao et al, 2008;Guttilla et al, 2012;Wei et al, 2014a Let-7 Reporter assay, mRNA/protein expression, and function study Zhao et al, 2011 miR-18a Reporter assay, protein expression, association and function study Liu et al, 2009 miR-18a/b, -19b, -20b, -193b, -206 Reporter assay, protein expression Castellano et al, 2009;Leivonen et al, 2009b miR-145 Reporter assay, mRNA and protein expression, and function study Spizzo et al, 2010 miR-22 Reporter assay, protein expression, and function study Pandey and Picard, 2009;Xiong et al, 2010 miR-206 Reporter assay, protein expression, and function study Adams et al, 2007;Kondo et al, 2008 miR-27a via zinc finger and BTB domain containing 10 (ZBTB10) Li et al, 2010a miR-219-5p Reporter assay, mRNA/protein expression, association and function Huang et al, 2015 miR-135b Reporter assay, mRNA and protein expression Aakula et al, 2015 NFE2L2/Nrf2 miR-144 Reporter assay, mRNA and protein expression, and function study Sangokoya et al, 2010 miR-28 Reporter assay, mRNA and protein expression Yang et al, 2011 miR-200a (Activation) via Kelch-like ECH-associated protein 1 (Keap1) Eades et al, 2011;Yang et al, 2014 miR-153, -27a, -142-5p, -144 Reporter assay, mRNA and protein expression, and function study Narasimhan et al, 2012Narasimhan et al, , 2014 Protein expression, and function study Singh et al, 2013 miR-507, -634, -450, -129-5p Reporter assay, mRNA and protein expression, and function study Yamamoto et al, 2014 miR-34a mRNA and protein expression Huang et al, 2014 miR-340 Reporter assay, mRNA and protein expression, and function study Shi et al, 2014a miR-141 via Kelch-like ECH-associated protein 1 (Keap1) …”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%
“…Beyond translation, Keap1 is silenced through mechanisms such as microRNA repression (i.e. miR-141, miR-200a) (Eades et al, 2011), or autophagosome regulation (i.e. p62/SQSTM1) , resulting in ineffective Nrf2 repression.…”
Section: Endogenous Nrf2 Upregulatory Mechanismsmentioning
confidence: 99%